2002
DOI: 10.1021/la020614c
|View full text |Cite
|
Sign up to set email alerts
|

Probing of the Reaction Progress at a PMMA/PS Interface by Using Anthracene-Labeled Reactive PS Chains

Abstract: The progress of the interfacial reaction of polystyrene chains end-capped by a primary amine (PS-NH2) and PMMA chains end-capped by an anhydride (PMMA-anh) has been monitored by SEC-UV, by using anthracene-labeled polystyrene chains (anth-PS-NH 2) as a probe. Assemblies of an anth-PS-NH2 layer and a PMMA-anh layer were annealed at 200 °C for various periods of time. The interfacial reaction rate depends on the molecular weight (MW) of the reactive precursors in relation to the χN value of the chains. For chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
81
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 25 publications
10
81
1
Order By: Relevance
“…Therefore, the interfacial reaction is not solely determined by the diffusion of the functionalized polymer to the reactive interface. The reaction limited nature of similar interfacial reactions 27,28,31,57,60,61,65,66 has also been observed.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Therefore, the interfacial reaction is not solely determined by the diffusion of the functionalized polymer to the reactive interface. The reaction limited nature of similar interfacial reactions 27,28,31,57,60,61,65,66 has also been observed.…”
Section: Resultsmentioning
confidence: 70%
“…As mentioned above, most studies on the interfacial reaction at a polymer/ substrate or polymer/polymer interface were found to be reaction-controlled. 27,28,31,57,59,61,65,66 However, diffusion-controlled processes have been observed. For example, Harton et al 67 studied an interfacial reaction for a highly reactive complementary polymer pair at a low annealing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…This effect cannot be associated with the diffusion of the low molecular weight chains, since several studies evidenced that the interfacial reaction is controlled by the collision efficiency of the reactive groups and not by diffusion. Instead, Yin [55] proposed that the dependence of the reactivity on the molecular weight could be related to the interfacial thickness, as shown by Helfand and Tagami [73] and Broseta [74]. As described before, the reaction rate at the interface usually decreases dramatically as the critical concentration of interfacial copolymers is formed.…”
Section: Effect Of the Reactive Precursor Molecular Weightmentioning
confidence: 99%
“…Various studies relating to the morphology of static reactive interfaces demonstrated that these can become highly irregular after the reaction between the reactive precursors [55][56][57][58]. A few researchers [59][60][61][62][63] measured the interfaces irregularity as a function of the reaction time and compared them with the S values determined experimentally.…”
Section: Effect Of Interfacial Reactions On the Interface Morphologymentioning
confidence: 99%
See 1 more Smart Citation